Fulfilling the Demands of Digitalization in the Accounting Profession: A Technological Knowledge Assessment for Future Accountants - Awang, Yunita; Taib, Azuraidah; Shuhidan, Shazalina Mohamed; Rashid, Norfadzilah; Hasan, Mohd Sidki (Indonesian Journal of Sustainability Accounting and Management, 2023)
As the digital world continues to grow, both finance and accounting practitioners, as well as future accountants, must embrace the digital transition in order to remain relevant. Thus, this study attempts to assess the technological knowledge for future accountants and evaluate its relationship with the digitalization of the accounting profession. Employing a non-probability purposive sampling approach, online questionnaires were distributed to accounting interns from the top six public universities for accounting and finance in Malaysia. This study found a moderate level of knowledge about technology among the respondents. Meanwhile, there is a significant and weak positive relationship between knowledge about technology and the digitalization of the accounting profession. Future research could be extended to accounting students at all universities and use alternative research methodologies, such as in-depth interviews, to improve the assessment of future accountants’ technological knowledge.